Customers emotional blackmail and reduce it the new product- study of the opinions of a sample of customers who deal with peak economy for household items in najaf al Ashraf - الطائي, يوسف حجيم; عبيد, حيدر جاسم (Journal of Economics and Administrative Sciences, 2017)
The challenges facing today's multi-customer and this is due to the multiplicity of products and speed in launching new products so search came to reveal the  reveal the of the new product classification standards through a relationship (good products, low interest products, useful products and products desired) and the customer emotionally blackmail through deportation (fear, obligation and guilt). dentified the problem of the research in several questions focused on the nature of the relationship between the variables of research, and for that outline supposedly to search it expresses the head of one hypothesis and branched out of which four hypotheses subset, but in order to ensure the validity of the assumptions have undergone all multiple tests to ensure their validity, as it has been relying on the resolution as a way to get the data, Use Find descriptive analytical method as a way to search according to a random sample consisted of (315) as The questionnaire was distributed to customers as a sample to evaluate the search variables, either the research community was the (1500) customer and representing 21%, and extracted the results using statistical software (SPSS Pct v.16). The research found a set of conclusions that customers of the most important research sample is not clear they have the four categories above a way that makes those difficult emotionally exploited by the marketer.